Operational monitoring and evaluation of a compact sanitary wastewater treatment plant: UASB reactor followed by submerged aerated filter - Ribeiro, Jaqueline Cardoso [UNESP] (2018)
Compact Wastewater Treatment Plants (CWTPs) are a great alternative to implementing decentralized sewage systems that can serve small communities. However, such systems are still poorly used and there is little experience regarding their operation. Based on such demand, this research aimed to evaluate the efficiency and to conduct an operational monitoring of a CWTP composed by an Upflow Anaerobic Sludge Blanket (UASB) reactor, followed by Submerged Aerated Filter (SAF), in the city of Uru, São Paulo, Brazil. During the research, the system proved to be a viable alternative for small communities, because it showed good efficiency, with average removal values of biochemical oxygen demand (BOD5) and chemical oxygen demand (COD) of 91 and 85%, respectively. The monitoring carried out during the research also contributed to general improvements in the system.